2020
DOI: 10.1186/s12885-020-07487-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-existing cardiovascular disease on treatment patterns and survival outcomes in patients with lung cancer

Abstract: Background Baseline cardiovascular disease (CVD) can impact the patterns of treatment and hence the outcomes of patients with lung cancer. This study aimed to characterize treatment trends and survival outcomes of patients with pre-existing CVD prior to their diagnosis of lung cancer. Methods We conducted a retrospective, population-based cohort study of patients with lung cancer diagnosed from 2004 to 2015 in a large Canadian province. Multivariable logistic regression and Cox regression models were constru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our results postulated the upper hand of cardiovascular and cerebrovascular diseases as a non-cancer-related cause of death in patients with BM, which was consistent with previous studies. Batra et al concluded that patients with lung cancer and pre-existing cardiovascular disease had a higher risk of dying from non-cancer causes than cancer causes ( 18 ). Compared to the general population, the SMR of fatal heart disease in cancer patients was up to 2.24 (95% CI : 2.23–2.25) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results postulated the upper hand of cardiovascular and cerebrovascular diseases as a non-cancer-related cause of death in patients with BM, which was consistent with previous studies. Batra et al concluded that patients with lung cancer and pre-existing cardiovascular disease had a higher risk of dying from non-cancer causes than cancer causes ( 18 ). Compared to the general population, the SMR of fatal heart disease in cancer patients was up to 2.24 (95% CI : 2.23–2.25) ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that the effect of chronic cardiac comorbidities on mortality is dominant in early stages of lung cancer seems most plausible. Data on 95 167 NSCLC patients showed that cardiovascular disease can increase mortality when the cancer stage is in the range I-III B, while it is not important for survival in stage IV (10). Worse prognosis was associated with concomitant heart failure, myocardial infarction, and arrhythmias diagnosed during follow-up, although the risk still varied depending on the stage of the disease and the treatment method.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective cohort studies have shown that cancer-related mortality rates for biologically aggressive malignancies exceed those for comorbidities (8,9). Batra et al showed that patients with lung cancer and CV diseases were less likely to receive oncological treatment, whether chemotherapy, targeted therapy or radiotherapy (10). It has also been shown that prior CV disease increases the risk of cancer-unrelated death (HR = 1.48; p < 0.0001) and does not contribute to cancer-related mortality.…”
Section: Charlson Comorbidity Index (Cci)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, concerns regarding treatment-related cardiotoxicity may serve as obstacles to receiving proper cancer treatment. For example, a recent study noted that pre-existing CVDs, which is known to be a risk factor for cardiotoxicity, were related to lower odds of receiving chemotherapy, radiotherapy, and surgery for lung cancer (Batra et al, 2020). This may be because these patients were considered too frail to receive standard treatments or at an intensified risk for cardiotoxicity due to cancer treatments.…”
Section: Introductionmentioning
confidence: 99%